Pengaruh kualitas produk dan harga terhadap kepuasan konsumen pembelian online - Novika Rahmatika; Deni Ramdani (Universitas Negeri Padang, 2021)
Generation Z and Millennials become the population that dominates Indonesia dominated by productive age. 90 percent of goods sold online are imported products from foreign countries, there are three marketplace platforms that are most often used by online buyers of Indonesian citizens, namely Alibaba and Aliexpress from China, and Amazon from the United States. Data collection techniques that are secondary and primary, the data used in this research is through kuisoner / questionnaire and literature studies. The data taken is crossection data. In this study the data analysis technique used is the Validity Test, a Realibility Test to test the given custody of a predetermined indicator. The results of the study here state that the product quality variable has no effect on customer satisfaction, so Hypothesis 1 is rejected. While the price affects the customer satisfaction variable so that hypothesis 2 is accepted. Product quality and price simultaneously affect customer satisfaction.